Optimization of end milling parameters and determination of the effects of edge profile for high surface quality of AISI H13 steel by using precise and fast measurements - Durakbasa, M. Numan; Akdogan, Anil; Vanli, Ali Serdar; Bulutsuz, Asli Gunay (ELSEVIER SCI LTD, 2015)
This work researches end milling process parameters and also various coating effects on surface quality of the machined parts experimentally. It especially focuses on the effects of tip radius of the tools on the machined surface quality with modern and precise measurement techniques and methods. Taguchi, design of experiments method, was used to determine the optimum processing parameters like cutting speed and depth of cut. Additionally the best coating material which combined with different tool radiuses to obtain high surface quality for the end milling process of AISI H13 hot work steel were investigated. The conducted statistical tests were indicated that coating type is the most effective parameter for the surface roughness according to the selected parameters and their levels. The created mathematical model can explain the 0.90 proportion of the total variability in R-a, arithmetical average surface roughness parameter. High precisely captured optical images indicate tip radius wear effects on surface quality clearly. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: End milling; Parameter optimization; Surface quality; Precise measurement; CUTTING PARAMETERS; TAGUCHI METHOD; SPEED; ROUGHNESS; GEOMETRY; DESIGN; RADIUS; Engineering; Instruments & Instrumentation